Optimization of Tsunami and Earthquake Awareness Through Digital Mapping Using a Decision Support System with Simple Additive Weighting (SAW) in Padang City - Vadreas, Andrew Kurniawan; Fryonanda, Harfebi; Arsyah, Ulya Ilhami; Maulana, Raihan Efel; Nirad, Dwi Welly Sukma (ABEC Indonesia, 2024)
Padang is a city that is prone to earthquakes and tsunamis due to its location between the India and Asia plateson the west coast and being crossed by the Great Sumatran fault. The Padang coastal region is a strong source ofearthquakes and tsunamis. Despite having experienced earthquakes in 2006, 2007, and 2009, Padang still facesdifficulties in managing tsunami evacuation because of the lack of infrastructure and straight roads from the coast tohigher ground. The presence of rivers in Padang causes the tsunami waves to be concentrated within a 200-meter radiusand the evacuation routes are hindered by the presence of bridges that are not durable against tsunamis and earthquakes.Additionally, traffic congestion after an earthquake exacerbates the evacuation problems. This study aims to map the riskand potential of earthquakes and tsunamis in Padang 3 KM from the coast by comparing population and building datawith the availability of shelters. The Simple Additive Weighting (SAW) method, as part of Geographic InformationSystem, is used to analyze demographic data and shelter locations. The results show that Koto Tangah is the area with thehighest risk level for earthquakes and tsunamis.